Inventory Of Beras rendang Recipes As Traditional Food In Fifty City District, West Sumatera - Anantaya, Frichicila Tri; Gusnita, Wiwik; Insan, Ranggi Rahimul (Universitas Negeri Padang, 2024)
Differences in selecting ingredients, measuring ingredients and techniques for making rendang rice mean that the quality produced is also different. The basic technique for making rendang rice is that the sticky rice is mashed, then the coconut milk, granulated sugar and vanilla are cooked until it thickens until it becomes candied. This research aims to describe the standardization of recipes, methods of making and the quality of rendang rice in Nagari Padang Japang, LimaPuluh City Regency. This type of research is qualitative and quantitative research using mixed methods. The data in this research uses primary data. Qualitative data collection techniques are observation, interviews, documentation and quantitative data collection techniques are organoleptic test questionnaire format. Qualitative data analysis techniques use three activity streams, namely: data reduction, data presentation, drawing conclusions and quantitative data analysis techniques using the formula (Mx=∑ x / N), data validity, testing the validity of qualitative data, namely: extended participation, diligent observation, and triangulation. Based on the research results, 3 rendang rice recipes were obtained. The results of the organoleptic test obtained the highest score by Mrs. Misna from Jorong Ampang Gadang with an average score of 19.6. Standardization of rendang rice recipes is carried out by organoleptic tests to obtain good quality rendang rice including: shape of rendang rice (neat and uniform), color of rendang rice (white), aroma of rendang rice (fragrant), texture of rendang rice (soft) and taste of rendang rice ( sweet).